(untitled) (Polifonia, 2014)
ABSTRACT: In this paper we examine the way the Brazilian Indigenous subaltern identity is represented verbally and visually in one of the most widely read newspapers in Brazil, Folha de São Paulo. Our objective is to show that these representations are never neutral or objective but are constructed inside the dominant ideology that tends to attribute to the Indigenous identity pejorative characteristics. The analysis of a report on the invasion of a luxurious hotel by the Indigenous Tupinamba tribe and the interpretation of its accompanying photograph offer an insight on the mechanisms the media uses in order to disqualify Indigenous political movements. The insight of Critical Discourse Analysis and Critical Visual Literacy can cause ruptures in the representations the media make of realities and can lead to a better understanding of the contextualizing nature of the construction of any identity. KEYWORDS: Representation, subaltern, identity RESUMO: Neste artigo examinamos a forma como a identidade Indígena subalterna Brasileira é representada verbalmente e visualmente em um dos jornais mais lidos do Brasil, Folha de São Paulo. Nosso objetivo é mostrar que essas representações nunca são neutras ou objetivas, mas são construídas no interior da ideologia dominante que tende a atribuir características pejorativas à identidade Indígena. A análise de uma reportagem sobre a invasão de um hotel de luxo pela tribo indígena Tupinambá e a interpretação da fotografia que a acompanha oferecem um melhor discernimento dos mecanismos que a mídia utiliza para desqualificar os movimentos políticos indígenas. A perspectiva da Analise Crítica do Discurso e o Letramento Crítico Visual podem causar rupturas nas representações que a mídia faz da realidade e podem levar a uma melhor compreensão da natureza contextualizada da construção de qualquer identidade. PALAVRAS-CHAVE: Representação, subalterno, identidade